2022
DOI: 10.1177/03795721221078361
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Trial of Quintuple Fortified Salt—Salt Fortified With Iodine, Iron, Folic Acid, Vitamin B12, and Zinc—Among Consumers in New Delhi, India

Abstract: Background: Micronutrient deficiencies are a cause of significant public health burden and loss of gross domestic product, especially in developing countries. Multiple fortified salt can potentially address this challenge at scale and in a cost-effective manner. Objective: This laboratory-based sensory trial evaluated the acceptability of quintuple fortified salt (Q5FS), that is, iodized salt (IS) fortified with additional 4 micronutrients: iron, folic acid, vitamin B12, and zinc. Iodized salt and double forti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, a study attempting to simultaneously fortify salt with iodine, iron, and zinc reported that iodine was lost when zinc was added in the spray solution but researchers observed a viable outcome due to the encapsulation of zinc and iron [ 51 ]. Another study at the University of Toronto successfully developed quintuple fortified salt containing folic acid, vitamin B-12, iron, and zinc using microencapsulation technology on iodized salt [ 52 ]. This may cause potential difference in the feasibility and cost-effectiveness of DFS with iodine and folate compared with fortification with the inclusion of iodine, folic acid, and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study attempting to simultaneously fortify salt with iodine, iron, and zinc reported that iodine was lost when zinc was added in the spray solution but researchers observed a viable outcome due to the encapsulation of zinc and iron [ 51 ]. Another study at the University of Toronto successfully developed quintuple fortified salt containing folic acid, vitamin B-12, iron, and zinc using microencapsulation technology on iodized salt [ 52 ]. This may cause potential difference in the feasibility and cost-effectiveness of DFS with iodine and folate compared with fortification with the inclusion of iodine, folic acid, and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…By utilising dried fish powder as its primary ingredient, ComFA+Fish is a nutrient-dense, locally accessible product that can easily be added to traditional dishes that family members are already used to consuming, including infants and young children who are in the complementary feeding stage. It is expected that this approach also helped ensure that the ComFA+Fish dishes received high scores for overall acceptability, as this is an attribute that Puri et al (2022) argue is more important ‘from the consumer point of view’ than are individual sensory attributes ( 41 , 5 ) .…”
Section: Discussionmentioning
confidence: 99%
“…For Sensory Panel I, we developed a technical lexicon for use by caregivers to evaluate five sensory attributes and two additional attributes of the four ComFAþFish dishes. Development of this lexicon and the panel's procedures were informed by Madrelle et al (2017) and others (40)(41)(42)(43) and the ComFAþFish dishes that were assessed included:…”
Section: Sensory Panel I Assessmentmentioning
confidence: 99%
See 1 more Smart Citation